2021
DOI: 10.3389/fneur.2021.608188
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cognitive Impairment After Stroke: Validation of the Chinese Version of the Quick Mild Cognitive Impairment Screen

Abstract: Background: Screening for post-stroke cognitive impairment (PSCI) is necessary because stroke increases the incidence of and accelerates premorbid cognitive decline. The Quick Mild Cognitive Impairment (Qmci) screen is a short, reliable and accurate cognitive screening instrument but is not yet validated in PSCI. We compared the diagnostic accuracy of a Chinese version of the Qmci screen (Qmci-CN) compared with the widely-used Chinese versions of the Montreal Cognitive Assessment (MoCA-CN) and Mini-Mental Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A total of 3640 articles were collected, of which 24 were eligible (Figure 1). 1820,27–47 All these studies were published between 2011 and 2022. The sample size varied from 34 to 521 participants, aged 17–95 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3640 articles were collected, of which 24 were eligible (Figure 1). 1820,27–47 All these studies were published between 2011 and 2022. The sample size varied from 34 to 521 participants, aged 17–95 years.…”
Section: Resultsmentioning
confidence: 99%
“…33 Six studies did not report the stroke type clearly. 29,35,38,42,45,47 Seven studies screened cognitive status in the acute/subacute phase, 29,31,32,34,37,41,44 11 in the non-acute phase, 1820,27,28,30,33,39,40,43,45 and 2 within 3 months of the stroke event. 36,42 The interval between stroke presentation and the assessment ranged from 2 weeks up to 13 years in one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding screening for cognitive impairment after stroke, Xu et al ( 6 ) compared the diagnostic accuracy of a Chinese version of the Quick Mild Cognitive Impairment (Qmci-CN) with a widely-used Chinese version of Montreal Cognitive Assessment (MoCA-CN) and Mini-Mental State Examination (MMSE-CN). They showed that the Qmci-CN is accurate in identifying post-stroke dementia and separating PSD from no-dementia PSCI.…”
mentioning
confidence: 99%